Pelestarian Budaya Bali Serta Pembelajaran Bahasa Asing di Daerah Pariwisata Batur Tengah Kintamani - Sukarini, Ni Made; Nadi, Ni Putu Sari; Darmayani, Kadek Dwi; Febriantari, A.A Ayu Mega Laksmi (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
With good and equitable education among the people in a country will help solve various social problems such as: ignorance and poverty so that people get a stable and directed life. In Indonesia itself, the government and society are still experiencing various challenges in efforts to improve education, causing various problems. After holding a meeting between group 8 members and the prebekel of Batur Tengah Village, namely: I Made Sasmika, SST obtained an agreement that the topics of community service in in the Education sector, namely Balinese Language, English, and Pasraman Kilat. One type of work program that has been designed by a group of 8 students of KKN Nusantara III I Gusti Bagus Sugriwa Denpasar State Hindu University is teaching activities carried out at SD Negeri 2 Batur and SD Negeri 7 Batur The community service activities carried out by the Group of Eight I Gusti Bagus Sugriwa Denpasar State Hindu University have proceeded according to the activity plan. Participants have been given education about Education and Culture. The results of the activities obtained were that participants understood well the material presented, and were able to make several Hindu ceremonial devices, namely: Canang Sari, Kwangen, Kulit Tipat, Karawista, dan Pancak. This will be used as an additional experience and indirectly it is expected that children's love for Balinese culture will increase.